POTENSI EKSTRAK DAUN SIRIH MERAH (Piper ornatum) DALAM MENGHAMBAT PERTUMBUHAN Pseudomonas aeruginosa SECARA in vitro - Nida Nabila Rahmah, (2020)
Red betel (Piper ornatum) has been used widely as herbal medicinal plant by Indonesian. This plant act as antibacterial and had been used to treat many illness. This study aim to investigate the potential of red betel extract to the growth of Pseudomonas aeruginosa. P. aeruginosa is aerob obligate negative-gram rod-shaped bacteria. This bacteria invades blood streams, lungs, and other body parts/organs. This study is experimental studies using post test only control group's design. This experiment was done in Fakultas Kedokteran Universitas Pembangunan Nasional "Veteran" Jakarta's microbiology lab. The result of this study is it was found that the means of red betel's inhibitory diametre in 40%, 50%, 60% and 70% concentration respectively are 6.7mm, 8.7mm, 4.1mm, 4.1mm. According to Davis and Stout, the red betel's inhibitory diametre in 40% and 50% concentration are categorized as moderate inhibitory diametre, while at 60% and 70% are weak inhibitory diametre. Statistic test had been used in this study was Kruskal Wallis test followed by Mann Whitney test. This test was choosed because the data distribution wasn't normal, P= 0,024 (p<0,05). The result from the test showed that there is significant difference, P= 0,006 (P<0,05), between 40% concentration to positive control and 50%, 60% and 70% concentration to positive control. The conclusion of this study is red betel extract has antibacterial potential to P. Aeruginosa with moderate inhibitory at 40% and 50% concentration and weak inhibitory at 60% and 70%.